The ROS/CaMK II/β-Catenin Signaling Axis Affects the Osteogenic Potential of BMSCs and Disrupts Implant Osseointegration: An In Vitro Study - Jiaqi Ding; Kai Dong; Delong Niu; Wenjie Qiu; Wenjuan Zhou; Zhonghao Liu (International Journal of Dentistry)
Conclusions: In summary, BMSC osteogenesis on titanium surfaces is suppressed by HG–induced oxidative stress via the ROS/CaMK II/β-catenin signaling axis, which may subsequently impair implant osseointegration.